Do neighborhood characteristics contribute beyond individual demographics to cancer control behaviors among African American adults?. (February 2020) - Knott, Cheryl L.; Ghosh, Debarchana; Williams, Beverly Rosa; Park, Crystal; Schulz, Emily; Williams, Randi M.; He, Xin; Stewart, Kathleen; Bell, Caryn; Clark, Eddie M.
Highlights: Neighborhood social environment plays a role in some cancer control behaviors beyond individual demographics. Neighborhoods greater in racial diversity were associated with less smoking. Greater neighborhood income and home ownership were associated with less smoking. Greater resident age and income were associated with men's prostate cancer screening. Findings have implications for interventions to combat the impact of historical racism on cancer. Abstract: Background: Recent years have seen increased interest in the role of neighborhood factors in chronic diseases such as cancers. Less is known about the role of neighborhood factors beyond individual demographics such as age or education. It is particularly important to examine neighborhood effects on health among African American men and women, considering the disproportionate impact of cancer on this group. This study evaluated the unique contribution of neighborhood characteristics (e.g., racial/ethnic diversity, income) beyond individual demographics, to cancer control behaviors in African American men and women. Methods: Individual-level data were drawn from a national survey (N = 2, 222). Participants' home addresses were geocoded and merged with neighborhood data from the American Community Survey. Multi-level regressions examined the unique contribution of neighborhood characteristics beyond individual demographics, to a variety of cancer risk, prevention, and screening behaviors. Results: Neighborhood racial/ethnic diversity, median income, and percentage of home ownership made modest significant contributions beyond individual factors, in particular to smoking status where these factors were associated with lower likelihood of smoking (ps < .05). Men living in neighborhoods with older residents, and greater income and home ownership were significantly more likely to report prostate specific antigen testing (ps < .05). Regional analyses suggested different neighborhood factors were associated with smoking status depending on the region. Conclusion: Findings provide a more nuanced understanding of the interplay of social determinants of health and neighborhood social environment among African American men and women, with implications for cancer control interventions to eliminate cancer disparities.